FRP-confined concrete-encased cross-shaped steel columns: Concept and behaviour. (1st December 2017) - Huang, Le; Yu, Tao; Zhang, Shi-Shun; Wang, Zhen-Yu
Highlights: The details of a new hybrid column with a square FRP confining tube are presented. The novel feature of the column is the use of a cross-shaped steel section. A series of test results are presented to demonstrate the concept of the column. The concrete is very effectively confined despite the square shape of the column. Abstract: FRP-confined concrete-encased cross-shaped steel columns (FCCSCs) are a new form of hybrid columns recently developed at the University of Wollongong. An FCCSC consists of a square FRP outer tube, a cross-shaped steel section and concrete filled in between. This sectional configuration ensures that the concrete is very effectively confined despite the square shape of the column. In addition, the cross-shaped steel section serves as the ductile longitudinal reinforcement for loads in the two lateral directions and its possible buckling is constrained by the FRP outer tube and the concrete, leading to a column that is highly ductile. In this paper, results from a series of stub column tests are presented to demonstrate the concept of the new column form. The experimental program involved the testing of FCCSC specimens as well as four types of similar column forms, namely, square FRP-confined plain concrete columns (SFCPCs), circular FRP-confined plain concrete columns (CFCPCs), concrete-encased cross-shaped steel columns and square plain concrete columns. The test results confirmed the excellent performance of FCCSCs. The test results also showed that compared with the concrete in SFCPCs and that in CFCPCs, the concrete in FCCSCs has a much larger ultimate axial strain and a larger compressive strength, when the same FRP tube is used.